Hunt for slow slip events along the Sumatran subduction zone in a decade of continuous GPS data. Issue 12 (11th December 2015) - Feng, Lujia; Hill, Emma M.; Elósegui, Pedro; Qiu, Qiang; Hermawan, Iwan; Banerjee, Paramesh; Sieh, Kerry
Abstract: Slow slip events (SSEs) have been observed in GPS time series for many subduction zones worldwide but not in decade‐long GPS time series from the Sumatran GPS Array (SuGAr). An outstanding question has been whether SSEs have simply not occurred on the Sunda megathrust or whether they have been obscured by the prodigious number of earthquakes and their ensuing postseismic deformation within the time of geodetic observation. We remove all known tectonic signals from the time series to search for evidence of SSEs. The residuals are essentially flat at the centimeter scale. To search for signals at the millimeter scale we test various filtering and visualization techniques. Despite these efforts, we conclude that it is difficult to confirm that SSEs exist at this scale using the current data, although we do see a few suspicious signals. The lack of evidence for events may reflect SSEs occurring at a magnitude, location, or timescale that renders them undetectable with the current resolution of the SuGAr, that the properties of this megathrust are not conducive to SSEs, or because the megathrust is in an active period of the earthquake cycle. Key Points: No confirming evidence for slow slip events in continuous data from the Sumatran GPS Array Suspicious signals that resemble slow slip events exist but cannot be confirmed Slow slip events that are either too small or too large may go undetected